Friends, followers, peers, and posts: adolescents' in-person and online friendship networks and social media use influences on friendship closeness via the importance of technology for social connection - Al-Jbouri, Elizabeth; Volk, Anthony A.; Spadafora, Natalie; Andrews, Naomi C. Z. (Frontiers in Developmental Psychology, 2024)
With the proliferation of smartphones, social media access and use is ubiquitous. As such, many adolescent friendships now comprise both in-person and online contexts. Our paper explores the relationship between these contexts in two parts: the first is an exploratory comparison of inperson and online friendship networks with peers at school using descriptive social network analysis; the second, an investigation of how the use of different social media platforms relates to the importance placed on social media for connectedness and friendship closeness. Participants were 547 adolescents (M= 15.25 years, 52% male, 55% white) from 6 schools in Southern Ontario, Canada. Participants completed a peer nomination survey on their relationships with peers at school and a self-report survey on social media use. Results suggest that while in-person and online networks are largely overlapping, there are important differences between the two.Results from the path analyses suggest that length of cell phone usage, Instagram, Snapchat, and YouTube were positively associated with the importance placed on technology for social connection and that this importance was also positively associated with feelings of friendship closeness. Daily cell phone usage, Instagram, and Snapchat use were positively indirectly associated with friendship closeness through the importance of technology for social connection.Our findings also suggest slight gender differences, with daily time spent on a smartphone only significantly positively associated with the importance of technology for social connection for girls. Implications for future study are discussed.